2015
DOI: 10.1287/mnsc.2014.2074
|View full text |Cite
|
Sign up to set email alerts
|

A Dollar for Your Thoughts: Feedback-Conditional Rebates on eBay

Abstract: Abstract. We run a series of controlled field experiments on eBay where buyers are rewarded for providing feedback. Our results suggest that the feedback rate increases when a rebate is given, though the effect is small. Moreover, the nature of buyer feedback is influenced by rewards: buyers are more likely to give positive feedback following a high-quality transaction (fast shipping) and less likely to give negative feedback following a lowquality transaction (slow shipping). In sum, you can buy feedback but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(78 citation statements)
references
References 38 publications
3
74
1
Order By: Relevance
“…Particularly, Cabral and Li (2015) conducted field experiments on eBay and found that users do show reciprocity by decreasing the likelihood of leaving negative feedback when they receive rebates [20]. Other researchers have empirically studied the temporary crowding-out effect and find that reviewers…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, Cabral and Li (2015) conducted field experiments on eBay and found that users do show reciprocity by decreasing the likelihood of leaving negative feedback when they receive rebates [20]. Other researchers have empirically studied the temporary crowding-out effect and find that reviewers…”
Section: Introductionmentioning
confidence: 99%
“…Our study is also related to the new and growing literature on reputation system design in online marketplaces (Li and Xiao [2014]; Cabral and Li [2015]). To maintain performance, an online marketplace as a pure market intermediary needs to consider designs for both information disclosure and a reputation rating system.…”
Section: Related Literaturementioning
confidence: 93%
“…However, a later field experiment study reached a different conclusion: The provision of online reviews did not increase, although rebates were provided. To make things worse, there were far fewer negative reviews (Cabral and Li, 2015), which is puzzling.…”
Section: Related Literaturementioning
confidence: 99%